Martial law melodrama Lino Brocka's cinema politics - Capino, Jose B. (Quezon City Ateneo de Manila University Press, 2023)
"Lino Brocka (1939-1991) was one of Asia and the Global South's most celebrated filmmakers. A versatile talent, he was at once a bankable director of genre movies, an internationally acclaimed auteur of social films, a pioneer of queer cinema, and an outspoken critic of Ferdinand Marcos's autocratic regime. José B. Capino examines the figuration of politics in the Filipino director's movies, illuminating their historical contexts, allegorical tropes, and social critiques. Combining eye-opening archival research with fresh interpretations of over fifteen of Brocka's major and minor works, Martial Law Melodrama does more than reveal the breadth of his political vision. It also offers a timely lesson about popular cinema's vital role in the struggle for democracy"
The country and the city : social melodrama and the symptoms of autocratic rule -- "A thoroughly different kind of mother" : surrogate autocrats, restive youth, and the maternal melodrama -- The melodramatics of crime : film noir in the twilight of martial law -- Tales of unrelenting misfortunes : family melodrama and the 1980s economic crisis -- Men in revolt : two experiments in political cinema -- A dirty affair : political melodramas of democratization -- Picturing "a faggot's dilemma" : sexuality, politics, and a commerce in queer movies -- Coda : three non-endings.
Includes bibliographical references and index.
Keywords: Brocka, Lino -- 1939-1991 -- Criticism and interpretation; Motion pictures -- Political aspects -- Philippines -- 20th century